Objective Assessment of Lingual Nerve Microsurgical Reconstruction. Issue 8 (November 2018) - Biglioli, Federico; Lozza, Alessandro; Colletti, Giacomo; Allevi, Fabiana
Abstract : Abstract: Lingual nerve (LN) injury is one of the most serious consequences of oral surgery. Prompt microsurgical reconstruction of the nerve can alleviate most of those symptoms leading to satisfactory functional recovery. Thirty-five patients with partial to complete LN injury underwent surgery in the period between January 2006 and May 2015. All patients underwent a preoperative clinical and neurological evaluation with the assessment of lingual tactile and pain sensory thresholds and masseteric inhibitory reflex. All patients underwent explorative surgery and direct microneurorrhaphy of distal and proximal stumps in case of complete lesion, while the removal of traumatic neuroma and the following microneurorrhaphy of distal and proximal stumps of the injured nerve was performed in case of incomplete lesion. Nerve grafting has always been avoided because of distal stump mobilization obtained by severing the submandibular branch of the LN. All patients but 1 exhibited good recovery of tongue sensation, never complete, both clinically and electrophysiologically: recovery of the excitability of masseteric inhibitory reflex suppression components SP1 and SP2 was observed, often with increased latencies but consistent with a functional recovery. All patients feeling pain preoperatively experienced complete relief of algic symptoms. The early microsurgical approach is the most suitable choice for the treatment of LN injuries.